2011
DOI: 10.1128/aem.02668-10
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Lactobacillus plantarum IMDO 130201, a Wheat Sourdough Isolate, to Growth in Wheat Sourdough Simulation Medium at Different pH Values through Differential Gene Expression

Abstract: Sourdough is a very competitive and challenging environment for microorganisms. Usually, a stable microbiota composed of lactic acid bacteria (LAB) and yeasts dominates this ecosystem. Although sourdough is rich in carbohydrates, thus providing an ideal environment for microorganisms to grow, its low pH presents a particular challenge. The nature of the adaptation to this low pH was investigated for Lactobacillus plantarum IMDO 130201, an isolate from a laboratory wheat sourdough fermentation. Batch fermentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Thus, the origin of the flour may make a difference although the number of LAB in rye sourdough is assumed to be similar to that in wheat sourdough (Ercolini, 2013;Ercolini et al, 2013;Weckx et al, 2010). Alternatively, external factors such as temperature fluctuations could change microbial counts between breadmaking runs (Kurtzman and Robnett, 2003;Meroth et al, 2003a;Vogelmann and Hertel, 2011;Vrancken et al, 2011b). Finally, the microbial composition of the community may affect the microbial counts, as suggested by the low counts of yeasts in presence of T. delbrueckii observed for Bakery 1 and also in a Belgium sourdough (Scheirlinck et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the origin of the flour may make a difference although the number of LAB in rye sourdough is assumed to be similar to that in wheat sourdough (Ercolini, 2013;Ercolini et al, 2013;Weckx et al, 2010). Alternatively, external factors such as temperature fluctuations could change microbial counts between breadmaking runs (Kurtzman and Robnett, 2003;Meroth et al, 2003a;Vogelmann and Hertel, 2011;Vrancken et al, 2011b). Finally, the microbial composition of the community may affect the microbial counts, as suggested by the low counts of yeasts in presence of T. delbrueckii observed for Bakery 1 and also in a Belgium sourdough (Scheirlinck et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…At the same time, the low pH values implied a poor expression of the genes involved in carbohydrate degradation in L. plantarum IMDO 130201. The bacterium was directed toward survival at low pH by amino acid conversions rather than by relying on growth [112]. The same behavior was identified in L. sanfranciscensis LSCE1 response to pH 3.6 [15].…”
Section: General Steps Regarding a Virtual Fermented Food Processmentioning
confidence: 51%
“…Another example of the influence of the process on LAB metabolism has been widely described [112]. These Authors monitored the evolution of the gene expression of L. plantarum IMDO 130201 during a sourdough process.…”
Section: General Steps Regarding a Virtual Fermented Food Processmentioning
confidence: 99%
“…2.3-fold) than the control, while maintaining the maximum production value (6400 AU ml -1 ), without altering the maximum specifi c growth rate and the maximum reached value (Table 1). This increase in bacteriocin production may occur as a response to exposure to sub-lethal pressure conditions, as it has been previously reported that bacteriocin production is stimulated by various stress conditions (NEYSENS & DE VUYST, 2005;ZAMFIR & GROSU-TUDOR, 2009;VRANCKEN et al, 2011). Nevertheless, the enhancement of the bacteriocin production due to cells exposure to low pressure treatments needs to be further investigated.…”
Section: Acta Alimentaria 46 2017mentioning
confidence: 99%
“…It has been observed that production of bacteriocins is infl uenced by the bacterial growth phase (GARCIA et al, 2016), medium composition (HALAMI & CHANDRASHEKAR, 2005), and culture conditions (MATARAGAS et al, 2003). In addition, bacteriocin production can be induced by exogenous factors (NEYSENS & DE VUYST, 2005;ZAMFIR & GROSU-TUDOR, 2009;VRANCKEN et al, 2011) or exhibit auto-induction (HAKIM et al, 2007). Presently, little information is available about the effect of such exogenous factors, including low pressures, on the bacteriocin production.…”
mentioning
confidence: 99%